Molecular pathways of depression and antidepressant therapies for treatment resistant depression - MCGRORY, CLAIRE (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2020)
According to the World Health Organisation, depression is the most common psychiatric disorder. Despite this, the pathophysiology of depression is unclear. Electroconvulsive therapy (ECT) is the most acutely effective treatment available for severe, sometimes life-threatening, depression. However, its molecular mechanism of action is not understood. Ketamine is a newly emerging rapid antidepressant pharmacotherapy for treatment resistant depression, but its mechanism is also unclear. Advances in scientific techniques are aiding the discovery of novel targets for depression. A deep sequencing study of microRNAs in depression conducted by my lab identified two microRNAs that are altered in patients with depression. Three genes were identified as shared targets of these: VEGFA, E2F1 and SIRT1. Peripheral whole blood VEGFA mRNA levels were also increased in depression and decreased by ECT. Therefore, E2F1 and SIRT1 are genes of interest in depression and the molecular mechanism of ECT. Finally, a proteomics study by my lab identified PEDF as a protein of interest. PEDF was increased in medicated patients with depression and increased further by ECT. Therefore, I hypothesised that antidepressants may target PEDF. The first aim of this study was to carry out gene expression analysis of E2F1 and SIRT1 in patients with depression in comparison to healthy controls. qRT-PCR results showed that levels of both genes were lower in patients with depression, but this was not attenuated by ECT. With E2F1, there were no differences in levels among depressive subgroups (psychosis, polarity, response status) and there were no associations with depression severity as measured by the HAMD-24 rating scale. These results indicate that E2F1 may be a trait marker of depression but it is not useful as a clinical marker. With SIRT1, there were no significant differences among subgroups, but levels were lower in patients with bipolar depression in comparison to unipolar depression. Numbers in the bipolar group were small (n = 19); so repetition in a larger cohort may be of use. In patients who responded to ECT and attained remission, there was also a trend for a correlation between an increase in SIRT1 with ECT and a decrease in HAM-D24 scores. As correlation analysis was exploratory, this would also need repeating in a larger cohort. Finally, gene expression analysis was performed on blood and brains of rats treated with chronic and acute electroconvulsive stimulation (ECS). E2F1 mRNA was decreased specifically in the dentate gyrus, with no change in peripheral blood. Sirt1 was increased in the hippocampal formation alone, with no change in peripheral blood. These results indicate that both E2F1 and SIRT1 may have a role in the mechanism of ECT in the brain but which may not be translated to the periphery. The next aim of this study was to evaluate a role for PEDF in the mechanism of antidepressants using an in vitro model. Primary rat cortical neurons, astrocytes and microglia were cultured. Astrocytes were found to express the highest levels of Serpinf1 (PEDF) mRNA. Therefore, astrocytes were treated with fluoxetine, imipramine and noradrenaline for 30 minutes, 1, 3, 6, 12 and 24 hours. Only imipramine (at 24 hours) and noradrenaline (at 3 hours) significantly decreased Serpinf1 mRNA expression. However, neither antidepressant drug had an effect on PEDF secretion from astrocytes. Therefore, I concluded that PEDF may not have a role to play in the molecular mechanism of antidepressants in so far as could be discerned from studying primary cultures. PEDF, however, may have a role in other brain regions or it may have a peripheral role. The final aim of this study was to evaluate the effect of a single infusion of ketamine or midazolam on VEGFA, PEDF (SERPINF1), E2F1 and SIRT1 mRNA expression. Of note, PEDF and VEGF are both neurotrophic and also known to interact, with PEDF blocking VEGF to inhibit angiogenesis. The ratio of VEGFA to SERPINF1 was also evaluated, based on evidence from previous literature, as this may provide a measure of pathway activity. Samples from the KARMA-Dep pilot trial were used and depressed patients? peripheral whole blood samples were collected 60 minutes before and 4 hours after an infusion of ketamine or midazolam. Ketamine alone significantly increased VEGFA levels. SERPINF1 levels were lower following ketamine treatment but this was not significant. The VEGFA/SERPINF1 mRNA ratio was also significantly increased following ketamine. No change was found with E2F1 levels. SIRT1 levels were increased in both groups post infusion, which may be due to diurnal variation. Plasma levels of VEGFA and PEDF protein were also analysed but no changes were found. The findings in this thesis show that E2F1 and SIRT1 may not be useful clinical markers in depression but there may be a role for them in the CNS that could be investigated further using animal models. This work points to a possible role for VEGFA and SERPINF1 in the molecular action of ketamine treatment but replication in a larger sample set is required. This is the first report of a relationship between these two genes in treatment for depression, and provides an interesting link to the findings of the deep-sequencing study and proteomic study that this work is based on. The interplay between VEGFA and PEDF could be a new pathway of interest in the molecular mechanism of treatments for patients with depression.
APPROVED
Keywords: Depression; Electroconvulsive therapy; Ketamine; Gene Expression